Creative Problem-Solving Learning Model Assisted by Articulate Storyline 3 Media on Students' Mathematical Creative Thinking Ability - Disa Ramadhani; Rohantizani Rohantizani; Fitri Ayu Ningtiyas; Yeni Listiana; Nurul Afni Sinaga; M Mursalin (SAINTIS Publishing, 2025)
The low level of students’ mathematical creative thinking ability is the main focus of this study. Based on interviews and observations, students were found to have difficulties solving problems that require creative thinking. This research aims to investigate the effect of the Creative Problem Solving (CPS) learning model assisted by Articulate Storyline 3 media on students’ mathematical creative thinking ability. A quantitative approach was used with a quasi-experimental method and Non-Equivalent Control Group Design. The research sample consisted of two seventh-grade classes at SMP Negeri 2 Dewantara, with class VII-A as the experimental group and VII-B as the control group. The instruments included a mathematical creative thinking ability test and observation sheets for both teachers and students. Data analysis was conducted using the Mann Whitney non-parametric test. The results showed that the Asymp. Sig. (2-tailed) value was 0.001 0.05, indicating a significant difference between the experimental and control groups. Therefore, the CPS model assisted by Articulate Storyline 3 had a positive impact on improving students’ mathematical creative thinking. The model facilitated students in exploring ideas, thinking in alternatives, and developing open-ended problem-solving strategies, making it a relevant alternative for mathematics learning at the junior high school level.